PERTANGGUNG JAWABAN PERUSAHAAN TERHADAP PEKERJA YANG DIRUMAHKAN (WFH) BERDASARKAN UNDANG-UNDANG NO.13 TAHUN 2003 - Arifuddin Muda Harahap; Fahri Fahrozi; Niki Marjuki; M. Harmansyah Hsb; Selmaria Purba; Indah Maya Sari Ritonga; Elza Armaini; Vita Aliyana WS; Sri Atmadianti; Twina Resia (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
Analyzing the company's obligation to the laid-off employees is the goal of this study. In this study, concepts, pertinent instances, and a normative approach based on legal theory were used. With data presented as narratives and conclusions drawn based on the analysis's findings, this study used a qualitative writing technique. The study's findings led to changes in a few employment laws, including Law No. 13 of 2003, which replaced it as the primary employment law. This change prevented the term "at home" from being recognized, meaning that moving into someone's home is not the same as being fired.Regarding workers who have been laid off from the termination of employment but who still receive full pay and are subject to reduction, the company must engage in negotiations with the union or workers, which is addressed in a special set on the Employment Minister Manpower Letter Number: SE-05/M/BW/1998. Bipartite and tripartite negotiations can be used to resolve the problem of workplace conflicts with businesses.